How beliefs and unpleasant emotions direct cyberbullying intentions - Ferreira, Paula (2022)
This study aims to investigate the role of emotions and beliefs of perceived severity about cyberbullying behavior in the relationship between bystanders’ personal moral beliefs and their behavioral intentions in cyberbullying. A group of 402 fifth to twelfth graders (Mage ¼ 13.12; SD ¼ 2.19; 55.7% were girls) participated and we ran exploratory factorial analyses of the instruments. A group of 676 fifth to twelfth grade students (Mage ¼ 14.10; SD ¼ 2.74; 55.5% were boys) participated and we performed confirmatory factor analyses. A group of middle school students (N ¼ 397; Mage ¼ 13.88 years; SD ¼ 1.45; 55.5% girls) participated and we ran the final analyses aimed to test the research hypotheses. Results from self-report measures showed that unpleasant emotions mediated personal moral beliefs and adolescent bystanders’ intentions to help cybervictims. Normative beliefs of severity mediated the relation between personal moral beliefs and intentions to cyberbully others.